Case Report: Plasma Biomarkers Reflect Immune Mechanisms of Guillain–Barré Syndrome - Wu, Chia-Lun; Chao, Chung-Hao; Lin, Shun-Wen; Chien, Yu-Yi; Huang, Wen-Yi; Weng, Wei-Chieh; Su, Feng-Chieh; Wei, Yi-Chia (Frontiers in Neurology, 2021)
This case series reported a group of patients with Guillain–Barré syndrome (GBS) and their plasma cytokine changes before and after immunotherapy. We aimed to understand GBS's pathogenesis and pathophysiology through observing the interval differences of the representative cytokines, which were the thymus and activation regulated chemokine (TARC) for T-cell chemotaxis, CD40 ligand (CD40L) for cosimulation of B and T cells, activated complement component C5/C5a, and brain-derived neurotrophic factor (BDNF) for survival and regenerative responses to nerve injuries. The fluorescence magnetic bead-based multiplexing immunoassay simultaneously quantified the five cytokines in a single sample. From June 2018 to December 2019, we enrolled five GBS patients who had completed before–after blood cytokine measurements. One patient was diagnosed with paraneoplastic GBS and excluded from the following cytokine analysis. The BDNF level decreased consistently in all the patients and made it a potential biomarker for the acute stage of GBS. Interval changes of the other four cytokines were relatively inconsistent and possibly related to interindividual differences in the immune response to GBS triggers, types of GBS variants, and classes of antiganglioside antibodies. In summary, utilizing the multiplexing immunoassay helps in understanding the complex immune mechanisms of GBS and the variation of immune responses in GBS subtypes; this method is feasible for identifying potential biomarkers of GBS.